Aspek Hukum Tanggung Jawab Pemerintah Daerah Terhadap Pemberdayaan Masyarakat Lingkar Usaha Tambang - Goni, Christine J. J. G.; Karamoy, Roy V.; Musa, Altje Agustin (Nuansa Akademik: Jurnal Pembangunan Masyarakat, 2025)
This research aims to determine the legal aspects of local government responsibilities for empowering communities around mining areas in mining businesses. The research utilizes normative methods, including conceptual approaches, legislation, and empirical cases. The empowerment process for communities around mining areas must be implemented from the environmental permitting stage, through planning, implementation, and monitoring, to post-mining. Local governments are encouraging business actors to initiate social and economic recovery from the impacts of mining within their jurisdiction.